СИСТЕМА СТАБІЛІЗАЦІЇ РІВНЯ РІДКОГО МЕТАЛУ В УСТАНОВЦІ ДЛЯ ВИРОБНИЦТВА МЕТАЛЕВИХ ГРАНУЛ - Глухенький, О.І.; Гориславець, Ю.М.; Павленко, В.Є.; Павлов, В.Б.; Токаревський, А.В.; Тугаєнко , Ю.П. (Інститут електродинаміки НАН України, Київ, 2015)
For acting installation for manufacturing of metal granules in purpose to decrease the dispersion of granules the system of stabilization the level of liquid metal above the nozzle of electromagnetic batcher was developed and researched. It is offered to realize the stabilization be supporting in process a constant consumption of liquid metal pump of magnetodynamic type, included into installation structure. Experimentally investigated the possibility of controlling the flow rate of the pump by changing the absolute value and phase angle of the current of electromagnet pump. Based on the established advantages of phase control, semiconducting dephaser is developed to power the electromagnet pump, and system of automatic control of the pump with electromagnetic speed sensor of liquid metal was developed. Performance of the system and the ability to stabilize the metal level by maintaining constant consumption of liquid metal pump confirmed experimentally. References 6, figures 8.